Diseases panorama in major cool season pulse crops and their bio-intensive management strategies - Mishra, R K; Parihar, A K; Dixit, G P (Indian Farming, 2023)
Chickpea, lentil and field pea are the most important cool-season crops grown worldwide for their higher productivity and nutritional value. These crops are well known for their high protein, mineral and antioxidant properties. Cool season pulse crops are severely affected by several biotic and abiotic stresses at various growth stages, which hamper their production and productivity drastically. Among the biotic stresses, diseases like wilt, root rot, powdery mildew and rust are the most devastating yield-limiting factors, causing huge losses every year if the environmental conditions are favourable. Most of the cool season pulse crops are consumed directly as green vegetables and salads, so the chemical pesticides and fertilizers cause several detrimental effects and residue problems in humans, animals and wild life, and also directly pollute the environment. Hence, bio-intensive-based interventions are more appropriate, cost-effective and environment friendly approach to manage these major diseases of cool season pulse crops for higher productivity and nutritional security for a large population.